Familial aggregation of psoriatic arthritis. Issue 5 (4th June 2008) - Chandran, V; Schentag, C T; Brockbank, J E; Pellett, F J; Shanmugarajah, S; Toloza, S M A; Rahman, P; Gladman, D D
Abstract : Objectives: The aim of this study was to determine the recurrence risk of psoriatic arthritis (PsA) and uncomplicated psoriasis in first-degree relatives (FDRs) of patients with PsA. Methods: All available FDRs (full siblings, parents and children) of 100 consecutive consenting patients attending a PsA clinic were evaluated for the presence of psoriasis and PsA using a standard protocol. The protocol included a screening questionnaire, physical examination by a rheumatologist, and radiographic and laboratory assessment. The prevalence of PsA and psoriasis in FDRs of the index cases was determined, and the recurrence risk ratio (λ) was calculated, assuming a population prevalence of PsA of 0.25%, and a population prevalence of psoriasis of 2%. Results: The 100 probands had 533 relatives. Eighty-four of them were deceased and 53 were unavailable (age <16 years). Of the remaining 396 FDRs, 107 did not participate (living too far away/did not consent). Thus, 289/396 (73%) of the available FDRs participated in the study. There were 130 siblings, 108 parents and 51 children. The prevalence of PsA and psoriasis among FDRs was 7.6% and 15.2%, respectively. The λ1 was 30.4 for PsA and 7.6 for psoriasis. The prevalence of PsA and psoriasis in siblings was 7.7% and 17.7%, respectively. The λS was 30.8 for PsA and 8.8 for psoriasis. Conclusions: The recurrence risk ratio for both PsA and psoriasis is high in FDRs and siblings of patients with PsA. These results confirm that both PsA and psoriasis have a strong heritable component.